Challenges and Determinants of Digital Business Innovation Ideation: An Empirical Study of University Students’ Experience - Sholihah, Masyithoh Annisaush; Azmi, Afra Nabilah Taqiyyah (Innovation, Technology, and Entrepreneurship Journal, 2025)
This mixed‐methods study explores how undergraduate students in an Applied Digital Business program identify and develop innovation ideas, the barriers they encounter, and the institutional support they require. Survey and interview data reveal a consistent pattern: while most students recognise digital knowledge as critical for ideation, many struggle to transform concepts into validated prototypes, citing technical gaps and uncertainty over business‑model design. Technology trends and shifts in user behaviour emerge as the dominant catalysts for idea generation, yet diagnosing meaningful real‑world problems remains a central challenge. Qualitative insights highlight the need for structured mentoring, live market exposure, and interdisciplinary collaboration. The paper proposes three curricular interventions—studio‑based prototyping, an external mentor pool, and validation sandboxes with local SMEs—to bridge the ideation–execution divide. These findings enrich the discourse on student innovation capability and offer practical guidance for higher‑education programmes aiming to cultivate applied digital entrepreneurship.